A deep search for faint Chandra X-ray sources, radio sources, and optical counterparts in NGC 6752. Issue 2 (27th September 2021) - Cohn, Haldan N; Lugger, Phyllis M; Zhao, Yue; Tudor, Vlad; Heinke, Craig O; Cool, Adrienne M; Anderson, Jay; Strader, Jay; Miller-Jones, James C A
ABSTRACT: We report the results of a deep search for faint Chandra X-ray sources, radio sources, and optical counterparts in the nearby, core-collapsed globular cluster, NGC 6752. We combined new and archival Chandra imaging to detect 51 X-ray sources (12 of which are new) within the 1.9 arcmin half-light radius. Three radio sources in deep ATCA 5 and 9 GHz radio images match with Chandra sources. We have searched for optical identifications for the expanded Chandra source list using deep Hubble Space Telescope photometry in B 435, R 625, H α, UV 275, and U 336 . Among the entire sample of 51 Chandra sources, we identify 18 cataclysmic variables (CVs), 9 chromospherically active binaries (ABs), 3 red giants (RGs), 3 galaxies (GLXs), and 6 active galactic nuclei (AGNs). Three of the sources are associated with millisecond pulsars (MSPs). As in our previous study of NGC 6752, we find that the brightest CVs appear to be more centrally concentrated than the faintest CVs, although the effect is no longer statistically significant as a consequence of the inclusion in the faint group of two intermediate brightness CVs. This possible difference in the radial distributions of the bright and faint CV groups appears to indicate that mass segregation has separated them. We note that photometric incompleteness in the crowded central region of the cluster may also play a role. Both groups of CVs have an inferred mass above that of the main-sequence turnoff stars. We discuss the implications for the masses of the CV components.